Educação popular, educação do campo e saberes tradicionais : trilhas que se cruzam e entrecruzam na Feira Cantasol em Cláudia – MT - Andrioni, Ivonei (2021)
This thesis is the result of a research carried on the female and male producers and consumers of the Socio-solidary and Agroecological Marketing Beds System Fair (CANTASOL) in the city of Claudia, in the State of Mato Grosso. This research counted on a qualitative study based on theoretical-methodological approaches of dialectical historical materialism which used elements of participatory research. As research instruments, semi-structured interviews, observations, photographs and field diaries were used. The analysis of the study was done by means of data triangulation, articulating them with the theoretical contribution, as well as, the research objectives. The objective of this research was to understand how the CANTASOL fair materializes itself as a project of life production which opposed to the project of agribusiness production. As a thesis, it is assumed that the CANTASOL fair constitutes itself as an instrument that opposes to the advance of the agribusiness frontier and the hegemonic project of the capitalist type of production. In this sense, the associated and agroecological production and the socio-solidary trade may contribute to another project of society. The conclusions revealed the possibility of confronting the advance of the agribusiness frontier and construction of a society in which everyone works and lives from the fruits of their work, in which the labor force is not a commodity, in which decisions about the management of the means of production, what and how to produce and to whom the fruits of their labor are destined are taken by the production collectives.